Preparation and application of Ag plasmon Bi3O4Cl photocatalyst for removal of emerging contaminants under visible light - Long, Zeqing; Guo, Tingting; Chen, Chao; Zhang, Guangming; Zhu, Jia (Frontiers in Microbiology, 2023)
Recently, the photocatalytic degradation of emerging contaminants (ECs) in water has been extensively studied. In this study, a series of Ag-Bi3O4Cl plasmon photocatalysts were synthesized through the photo-deposition of Ag metal on the surface of Bi3O4Cl. The effects of plasmon modification on the performance of bismuth oxychloride were analyzed in detail. The introduction of Ag did not alter the morphology of the catalyst. With an increase in the Ag metal content, the number of oxygen defects on the catalyst surface tended to increase first and then decrease. Moreover, the plasmon resonance effect on the surface of the catalyst reduced the recombination of electron-hole pairs, enhanced the migration and separation ability of electrons and holes, and improved the light absorption efficiency. However, the presence of excessive Ag metal reduced the sites of Bi3O4Cl activity, which hindered the catalytic degradation of pollutants. The optimal Ag-Bi3O4Cl (Ag ratio: 0.025; solution pH: 9; dosage: 0.8 g/L) achieved 93.8% and 94.9% removal of ciprofloxacin and tetrabromobisphenol A, respectively. The physicochemical and photoelectric properties of Ag-Bi3O4Cl were determined via a series of characterizations. Finally, the electron transfer path, photocatalytic reaction mechanism, and biotoxicity of degradation products of the reaction process were revealed.